Agronomic and nutritional characteristics of three grass species in the southern region of Mexico - LÓPEZ-GONZÁLEZ, F; SÁNCHEZ-VALDÉS, J J; CASTELÁN-ORTEGA, O A; ALBARRÁN-PORTILLO, B; ESTRADA-FLORES, J G (The Indian Journal of Animal Sciences, 2015)
The study was conducted to evaluate the agronomic and nutritional characteristics of 3 grass species in the Zacazonapan municipality in the southern region of Mexico for one-year period. Three pastures were used, with a different grass species established in each of them: Cynodon plectostachyus, Paspalum notatum and Brachiaria decumbens. The agronomic variables evaluated were: net forage accumulation (NFA), and the amounts of stems, leaves, and live and dead matter. Also evaluated were protein content, neutral detergent fiber (NDF), acid detergent fiber (ADF), digestibility of organic matter (dOM) and metabolizable energy (ME). A randomized block design was used, and data was analyzed using variance analysis, with the Tukey's test used to compare treatment means. There were significant differences among the 3 grass species evaluated, as well as among the evaluation periods (June 2009 to May 2010). In relation to the nutritional variables, there were significant differences among the evaluation periods, but not among the 3 grass species evaluated. It was concluded that the nutrient contents of the grasses were similar and the accumulation of forages were greater during the time period with more precipitation.